1998
DOI: 10.1126/science.281.5375.424
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Transcription Elongation Complex in Escherichia coli

Abstract: During RNA synthesis in the ternary elongation complex, RNA polymerase enzyme holds nucleic acids in three contiguous sites: the double-stranded DNA-binding site (DBS) ahead of the transcription bubble, the RNA-DNA heteroduplex-binding site (HBS), and the RNA-binding site (RBS) upstream of HBS. Photochemical cross-linking allowed mapping of the DNA and RNA contacts to specific positions on the amino acid sequence. Unexpectedly, the same protein regions were found to participate in both DBS and RBS. Thus, DNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 15 publications
3
68
0
Order By: Relevance
“…The basis for our quantitative analysis is the structural and mechanistic model of the elongation complex (EC) (3,5,10,23), sketched in Fig. 1.…”
Section: Model Of Transcription Elongationmentioning
confidence: 99%
“…The basis for our quantitative analysis is the structural and mechanistic model of the elongation complex (EC) (3,5,10,23), sketched in Fig. 1.…”
Section: Model Of Transcription Elongationmentioning
confidence: 99%
“…In the RNA exit channel, the interactions between nascent RNA and pol II in the region between 10 and 17 nt are expected to be very strong (30), for it is known that such interactions contribute to the stability of an elongation complex in prokaryotic RNA polymerase. Recent structural studies on the complexes formed by TFIIB with pol II have shown that the N-terminal segment of TFIIB, termed the ''B finger,'' reaches into the catalytic center of pol II exactly through a groove (31)(32)(33)(34), once presumed to be the RNA exit channel and proved to be true in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Macromolecular interactions among DNA, RNA, and E. coli RNA polymerase in the elongation complexes have been mapped (2)(3)(4)(5). A double clamp model has been proposed for elongating E. coli RNA polymerase where DNA entry and RNA exit sites are directed opposite to each other in the same region (5).…”
mentioning
confidence: 99%